ANALISIS KOMPARATIF UX DESIGN PADA PLATFORM EDUKASI ONLINE - Hendry Agus Setiawan; Muhammad Rifqi Ma’arif; Chanief Budi Setiawan; Fajar Syahruddin (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2020)
User experience is the result of what the user feels and thinks when using a product or service, and makes the user experience subjective, therefore the user experience (user experience) can be tested in conjunction with other tests to get an objective assessment of the user when can be done directly with the product. This study will discuss the user experience using the User Experience Questionnaire and Focus Group Discussion methods. The process to be carried out is by using the Brainly and Quora applications obtained from the UEQ and FGD test questionnaires through interviews and data interviews from questionnaires. Based on the results of this study, the results of the analysis and comparisons with UEQ and FGD were obtained. The first test objectively used direct testing to respondents using the UEQ questionnaire which has 6 scales, namely: attractiveness, efficiency, perspective, dependability, stimulation and novelty, which are given to 11 respondents. Second, subjective testing using Focus Group Discussion for perceptions and more detailed user problems with interviews. From the second test conducted, it can be denied that the Brainly application is superior to Quora.